UV–Spectrophotometric Method Development and Validation of Acamprosate Calcium by Absorption Maxima Method in Bulk and Tablet Dosage Form - Nagras, M. A.; Kandharkar, K. V. (Asian Journal of Pharmaceutical Research and Development, 2014)
A simple, rapid, accurate, precise, specific and economical spectrophotometric method for estimation of Acamprosate calcium in tablet dosage form has been developed. Beer-Lambert’s law was followed in the concentration range of 0.4 – 1.4 μg/ml (r2= 0.999). LOD and LOQ were found to be 0.013914 µg/ml 0.042614 µg/ml respectively. The method was validated by determining its accuracy and precision which proved suitability of the developed method for the routine estimation of Acamprosate calcium in solid dosage form.